Answer:
11
Step-by-step explanation:The radius will always be half of the diameter therefore it will be 11
Multiply the bracket by 6
6(-p+8)= -6p + 12
-6p+48= -6p+12
Move -6p from right side to left side
Sign changes from -6p to +6p
-6p+6p+48= -6p+6p+12
48= 12 ( No solution )
Answer : No solution
ok first you need to add e and 4 and get 95 out of haha
Answer:
1, 2, 3, 7, 10
Step-by-step explanation:
Answer:
64k^2 - 16k +1
Step-by-step explanation:
We can rewrite this as
(-8k+1) ^2
We know that (a+b)^2 = a^2 +2ab +b^2
Let a = -8k and b = 1
(-8k+1) = (-8k)^2 +2*(-8k)(1) + 1^2
=64k^2 - 16k +1